2019
DOI: 10.1002/cjce.23456
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of hydrodynamics and bubble size distribution of an external loop airlift reactor

Abstract: The most important factors influencing the performance of an external loop airlift reactor (ELALR) are local hydrodynamics and bubble size distribution (BSD). In this work, we studied the hydrodynamic characters and BSD in a laboratory scale ELALR. The velocity field of the riser was captured using the particle image velocimetry (PIV) technique and the bubble size distribution (BSD) was determined by digital image analysis (DIA). The results of the PIV measurement show that the flow has an unsteady structure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 37 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…Lu et al studied the hydrodynamic characters in a laboratory scale ALR by the experimental method, the velocity field was measured by using the particle image velocimetry technique, and the bubble size distribution was obtained by digital image analysis. The experimental results showed that the liquid flow had an unsteady structure and the wake oscillation of the bubble was asymmetrical, as the superficial gas velocity increased, the probability density function curve of bubble size changed from unimodal to bimodal [16]. Luo and Al-Dahhan adopted the CARPT technique to measure the distributions of liquid velocity, turbulent kinetic energy, and gas holdup in an ALR and observed that as the increase of the superficial velocity, the flow regime would change from bubbly flow to churn-turbulent flow [2].…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al studied the hydrodynamic characters in a laboratory scale ALR by the experimental method, the velocity field was measured by using the particle image velocimetry technique, and the bubble size distribution was obtained by digital image analysis. The experimental results showed that the liquid flow had an unsteady structure and the wake oscillation of the bubble was asymmetrical, as the superficial gas velocity increased, the probability density function curve of bubble size changed from unimodal to bimodal [16]. Luo and Al-Dahhan adopted the CARPT technique to measure the distributions of liquid velocity, turbulent kinetic energy, and gas holdup in an ALR and observed that as the increase of the superficial velocity, the flow regime would change from bubbly flow to churn-turbulent flow [2].…”
Section: Introductionmentioning
confidence: 99%